PELAKSANAAN EKSEKUSI JAMINAN FIDUSIA DALAM PENYELESAIAN KREDIT MACET DI PERUSAHAAN PEMBIAYAAN KENDARAAN SEPEDA MOTOR - Krismiyarsi S.H., M.H.; Dwi Kartika Dewi (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2012)
The implementation of fiduciary is regulated within Section 29 Regulation No. 42 Period 1999 about Fiduciary that declaring the implementation of fiduciary execution can be done by the executorial title implementation, public auction sale, or sale under the hand by both parties, however, in the practice many occurring debt collector doing expropriation on the road. The problem formulation in the research is: How does the implementation of fiduciary execution on bad debt settlement on motorcycle financing corporate? And how do the constraints is faced in the implementation of Fiduciary execution on bad debt settlement in motorcycle financing corporate? The research method uses normative juridical research type and with specification is analytical descriptive, main data comes from secondary data. The research result is obtained that: (1) the implementation of fiduciary execution on bad debt settlement in motorcycle financing corporate practically is done by: simple auction with persuasive approach stage, summation (warning), if does not success so the execution may be done. After the release of UUJF, toward the object of fiduciary is registered the execution can be conducted by using fiduciary certificate will released by Depkumham RI, whereas about it do not registered the implementation of material right warranty is based on Section 1131 Civil Code, (2) those constraints is faced in the implementation of fiduciary execution on bad debt settlement in motorcycle financing corporate as follows: Debtor escapes by obscuring fiduciary object in hiding or mortgaging, leasing, or transferring possession to third party, debtor falsifies data and self-identity and it business, so that it can make troublous as the execution will make toward Fiduciary object, warranty object has broken and do not appropriate to the appropriation.